Pengembangan E-Modul Berbasis Flipbook dengan Pendekatan Socio-Scientific Issue untuk Meningkatkan Kreativitas Siswa SMA pada Materi Sistem Peredaran Darah - Anggraeni Dwi Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to develop a flipbook-based e-module using the Socio-Scientific Issue (SSI) approach on the Circulatory System to enhance high school students' creativity. The background to this research arises from the limited learning media in schools, especially for abstract and complex materials, resulting in students tending to be passive and less creative in the learning process. The development process was conducted using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included nine students for the small group trial and thirty students for the field trial, as well as one biology teacher as the learning practitioner. Validation results by media experts, material experts, and biology teachers indicated that the flipbook-based e-module was categorized as highly valid, with an average feasibility percentage of 92.43%. Practicality testing based on student and teacher responses yielded percentages of 92.93% and 97.91%, respectively, which fall into the practical category. Effectiveness testing, through a comparison of pretest and posttest scores, showed an increase with an average N-Gain of 0.54 (moderate category), indicating that the use of the e-module was effective in enhancing student creativity in the learning material. Based on these results, the flipbook-based e module with the SSI approach was declared valid, practical, and effective as an innovative learning medium.
Reuploud repository Hasyim Juli 2026 Finalisasi 2 Juli 2026_Yudi
Keywords: Biology; Creativity; E-module; Flipbook; Socio-Scientific Issue (SSI).